Pertumbuhan dan Produksi Bawang Merah(Allium ascalonicum L.) Varietas Lokananta pada berbagai Ukuran Umbi G0 - Kurni Awan; Anthony Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to determine the effect and determine the best size of G0 tubers of red onion of Lokananta variety as planting material in the cultivation of shallots (Allium ascalonicum L. ). This research was carried out by the UPT Experimental Garden Faculty of Agriculture, Riau University, Pekanbaru. The study was conducted from September 2019 to November 2019. The study used a Completely Randomized Design (CRD) consisting of four treatments and five replications. The treatments used were tuber size> 10 g-12.5 g,> 7.5 g-10 g,> 5 g-7.5 g, and 2.5 g-5 g. The parameters observed were plant height (cm), number of leaves (strands), number of bulb per clump (fruit), bulb diameter (cm), fresh bulb weight per clump (g) and bulb weight worth keeping (kg). The results of the analysis were further tested usingmultiple range test Duncan's at 5% level. The results showed that the tuber size> 10 g-12.5 g was the best G0 bulb size in increasing plant height, number of leaves, number of bulbs, fresh bulb weight and bulb weight worth keeping. Keywords:Allium ascalonicum L., Bulb size, Lokananta variety